Estrutura e impacto da expansão da agroindústria canavieira sobre o mercado de terras no estado do Acre, Amazônia ocidental – Brasil - GOMES, Elói Biquer Silva Rosa (Universidade Federal do Pará, 2017)
This study deals with the question of the market of rural land in the Brazilian Amazon, for which was selected a specific region (the Lower Acre) as a case study. The choice of this area is due to the fact that it is developing and expanding heavily the agricultural activities with emphasis on the production of sugar cane in this region. This thesis aims to study the impact of the expansion of sugarcane on the market of rural land in the Region of Low Acre in the period 2007 to 2013. We analyzed the impact on the variation in land prices, the effects on the land use of the main food crops (rice, beans, corn and cassava) and the fluctuations of the price of ethanol practiced in the state of Acre. We used for this study the analytical database of UNICA, IBGE, FNP/Agrianual - which is a database that provides information on selling price of land for crops, pastures and prices of leases by states and regions in Brazil. The study allows us to conclude that in spite of the progress of the area occupied by the cultivation of sugar cane in the region, there has been a reduction of land occupation specifically for crops of beans and rice, but, on the other hand, there has been a considerable increase in the plantation areas of cassava and maize. The situation is quite worrying when it comes to the market of rural land in the region, especially after the start of agricultural activities of planting of sugar cane. There was a considerable enhancement of agricultural land, in the first years of the activities of the plantation. The prices in the region of Low Acre became to be one of the most expensive in the country, only behind the State of Amapá. The land designated for the pasture had higher valuations. This occurred because the areas of pasture are strongly linked to the activities of the plant of alcohol in the region. The agribusiness leased land that was reserved for pasture and the ranchers began to acquire/look for new areas for the creation of cattle. This increased demand for new land meant that they valorize above the national average. Consequently, this process has a major impact on the environment, affecting mainly the deforestation. The study showed that there was an increase in the rates of deforestation not only in the region, but throughout the State of Acre, including in areas such as environmental conservation, Extractive Reserves and indigenous lands. And finally, this study allows us to conclude that the hypothesis that the local production of ethanol would tend to influence the reduction in the price of alcohol in the State has not been confirmed. Paradoxically, even with the entry into operation of the plant (already more than three years), Acre continues to be State with the highest price of ethanol in the country, and the prospect is that even the increase of production in the upcoming years should not result in reduction of the price of ethanol because the trend is that the scenario in the domestic and international markets will remain turbulent in the coming years.